Implementation of Multicultural Education at Boarding School: Comparative Study - Tamyis Tamyis; Duski Ibrahim; Munir Munir (AL-ISHLAH: Jurnal Pendidikan, 2023)
This study aims to describe and analyze the differences in the implementation of multicultural education at the Hidayatul Mubtadiin Islamic Boarding School in Sidoharjo and the Al-Ishlah Sukapeace Islamic Boarding School. This study uses a qualitative approach. The data collection using observation, interview and documentation techniques. Meanwhile, for data analysis using three flow of activities, namely data reduction, data presentation and drawing conclusions. This study found that first, the implementation of multicultural education in both Islamic boarding schools was good, as seen from the role of the pesantren leaders. Second, the implementation of multicultural education at the Hidayatul Mubtadiin Sidoharjo Islamic boarding school with a cultural assimilation approach in the seven mottos of students, while the Al-Ishlah Islamic boarding school uses a self-development approach and self-development through formal and non-formal activities.